A Teacher's Writing Habit as Emotional Expression in a Demanding Teaching Routine - Rostina Rostina (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study explored how a teacher’s writing habit functions as emotional expression within a demanding teaching routine. Specifically, it examined four aspects like writing as emotional release, writing as reflective practice, writing within a demanding teaching routine, and writing as an emotional coping strategy. A qualitative single-case study design was employed. The participant was one female teacher at SD Negeri 060 Pekkabata, Polewali Mandar, Sulawesi Barat, who had a very hectic schedule including full-time teaching, administrative duties, and private tutoring. Data were collected through semi-structured interviews conducted via Zoom and WhatsApp chat, as well as document analysis of the teacher’s syllabus, lesson plans, blog, Instagram posts, journal book, and mobile phone notes. Thematic analysis was used to analyze the data. The findings revealed that writing served as a powerful emotional release, helping the teacher process anxiety and accept difficult situations. Reflective writing occurred primarily during professional training periods and motivated her to improve classroom practice. Despite her demanding routine, the teacher maintained a writing habit by using multiple platforms, writing during natural breaks, and prioritizing short, happiness-focused notes. She considered writing equally effective as talking to others for emotional expression and strongly recommended writing to fellow teachers. The study concludes that a flexible writing habit focused on emotional release and small positive moments can be a sustainable, low-cost coping strategy for teachers facing overwhelming professional demands. These findings have implications for teacher well-being program and teacher education.